ON MARCINKIEWICZ-ZYGMUND INEQUALITIES IN LP,³-SPACES, 0 < p } 1 - Al Saidy, Saheb K (Al-Nahrain Journal of Science, 2010)
We found the relationships between Marcinkiewicz-inequalities and linear trigonometric operators in the quasi-normed spaces Lp,m, 0 < p £ 1.